Manajemen Sekolah Adiwiyata (Green School) - Asep Priatna (Jurnal Soshum Insentif, 2020)
The issue of environmental pollution has come to the attention of the world community and has become a strategic issue in sustainable development, so it needs to have the support of all parties, including the government, the private sector and educational institutions. Integrated Junior High School Lampang, Subang Regency West Java Indonesia has been implementing the green school program since 2008 and in 2019 it was entrusted by the West Java Education Office to be proposed as a national level green school program. Some achievements as a green school implementing school are private schools that have obtained "A" (exellent) accreditation with a beautiful environment and are able to fulfil 4 (four) components, namely (1) environmentally sound policies, (2) implementation of environment-based curriculum, (3) participatory-based environmental activities and (4) management of environmentally friendly supporting facilities Keywords : Management, green school Isu pencemaran lingkungan hidup telah menjadi perhatian masyarakat dunia dan menjadi isu strategis dalam pembangunan berkelanjutan, sehingga perlu mendapat dukungan semua pihak baik pemerintah, sector swasta maupun lembaga pendidikan. SMPS Terpadu Lampang Kabupaten Subang telah melaksanakan program adiwiyata sejak tahun 2008 dan pada tahun 2019 diberi kepercayaan oleh Dinas Pandidikan Jawa Barat diusulkan sebagai Sekolah Adiwiyata (green school program) tingkat nasional. Beberapa capaian sebagai sekolah pelaksana green shcool adalah sekolah swasta yang telah memperoleh akreditasi “A” (Unggul) dengan lingkungan asri dan mampu memenuhi 4 (empat) komponen yaitu (1) kebijakan berwawasan lingkungan, (2) pelaksanaan kurikulum berbasis lingkungan, (3) kegiatan lingkungan berbasis partisipatif dan (4) pengelolaan sarana pendukung ramah lingkungan Kata Kunci : Manajemen, Sekolah Adiwiyata